Students Physical Activity Level, Students Learning Behavior, And Students Formative Class Evaluation, During Gymnastics Units Of Elementary School Physical Education Classes For 2nd And 3rd Graders - Suroto, (Pendidikan Dasar, 2006)
The purposes of this study were: (1) to describe the students physical activity level (PAL) measured by using direct observation and Lifecorder during gymnastics unit of PE classes for 2nd and 3rd graders, (2) to describe the students formative class evaluation (FCE) score towards their PE lessons, (3) to describe the students learning behavior (LB) during motor learning (A2) episodes of their PE lessons, and (4) to clarify the relationships among those variables during each of the units. Data were collected from 3 units of PE classes for 2nd graders at H elementary school in Ibaraki Prefecture, and from 1 unit of PE classes for 3rd graders at Z elementary school in Saitama Prefecture (Japan). The classes were videotaped using 6 seconds observe-record interval (ALT format), and evaluated using 2 measures: (1) students FCE, and (2) Lifecorder. Results indicated that: (1) the students PAL was averagely 2146 steps, 1.89 levels of intensity, and 72.2 % of A2 episodes for MV-PAL engagement; (2) the average total score of students FCE towards their PE lessons was 2.74; (3) averagely 62.6 % of motor learning (A2) episodes was used by students for engaged in learning activities; and (4) in general, the relationship among students PAL, students LB, and students FCE was not clear, but, inside the A2 episodes, the relationship between students PAL and students LB was significant.